Inositol phosphates in the environment - Turner, Benjamin L.; Papházy, Michael J.; Haygarth, Philip M.; Mckelvie, Ian D. (Philosophical transactions of the Royal Society of London. Series B. Biological sciences, 2002)
The inositol phosphates are a group of organic phosphorus compounds found widely in the natural environment, but that represent the greatest gap in our understanding of the global phosphorus cycle. They exist as inositols in various states of phosphorylation (bound to between one and six phosphate groups) and isomeric forms (e.g. myo, D-chiro, scyllo, neo), although myo-inositol hexakisphosphate is by far the most prevalent form in nature. In terrestrial environments, inositol phosphates are principally derived from plants and accumulate in soils to become the dominant class of organic phosphorus compounds. Inositol phosphates are also present in large amounts in aquatic environments, where they may contribute to eutrophication. Despite the prevalence of inositol phosphates in the environment, their cycling, mobility and bioavailability are poorly understood. This is largely related to analytical difficulties associated with the extraction, separation and detection of inositol phosphates in environmental samples. This review summarizes the current knowledge of inositol phosphates in the environment and the analytical techniques currently available for their detection in environmental samples. Recent advances in technology, such as the development of suitable chromatographic and capillary electrophoresis separation techniques, should help to elucidate some of the more pertinent questions regarding inositol phosphates in the natural environment.